STATISTICAL BOUNDS ON MULTIVARIABLE FREQUENCY-RESPONSE - AN EXTENSION OF THE GENERALIZED NYQUIST CRITERION - Cloud, D; Kouvaritakis, B (1986)
Statistical bounds for model parameters and corresponding system frequency-response limits are established. The results are extended to multivariable systems to produce an element-by-element characterization of system uncertainty. This uncertainty representation can be used to develop frequency-response bounds on the eigenfunctions of perturbed multivariable systems, thus producing system gain and phase information via a generalized Nyquist analysis. An application of the technique is presented using a two-input/two-output system.